2010
DOI: 10.2134/agronj2009.0402
|View full text |Cite
|
Sign up to set email alerts
|

Management of Small Grain Residues to Retain Legume‐Derived Nitrogen in Corn Cropping Systems

Abstract: A gronomy J our n al • Volume 102 , I s sue 3 • 2 010 895 ABSTRACT Minimizing N pollution from nonpoint agricultural sources is a management challenge in U.S. agriculture and in the Chesapeake Bay watershed. Th is 2-yr fi eld study examined the impact of C/N ratios, through modifi cation of straw residue, on the availability of small grain-hairy vetch (Vicia villosa Roth) derived N in a corn (Zea mays L.) cropping system. Treatments consisted of three levels of straw retention (0, 1, and 2 Mg ha -1 ), with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
6
10
0
Order By: Relevance
“…We found that cumulative proportional mass loss and N release increased with increasing hairy vetch/cereal rye biomass proportion in both years. This trend supports the findings of Starovoytov et al (2010), who reported that pure hairy vetch lost a greater proportion of initial mass by the end of the corn growing season than hairy vetch–small grain mixtures. On the other hand, Ranells and Wagger (1996) did not find clear trends in the cumulative proportional mass loss with hairy vetch/cereal rye biomass proportion, perhaps because their range of C/N ratios of residues was relatively narrow.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that cumulative proportional mass loss and N release increased with increasing hairy vetch/cereal rye biomass proportion in both years. This trend supports the findings of Starovoytov et al (2010), who reported that pure hairy vetch lost a greater proportion of initial mass by the end of the corn growing season than hairy vetch–small grain mixtures. On the other hand, Ranells and Wagger (1996) did not find clear trends in the cumulative proportional mass loss with hairy vetch/cereal rye biomass proportion, perhaps because their range of C/N ratios of residues was relatively narrow.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Ranells and Wagger (1996) did not find clear trends in the cumulative proportional mass loss with hairy vetch/cereal rye biomass proportion, perhaps because their range of C/N ratios of residues was relatively narrow. The proportional mass loss after one growing season ranged from 0.60 to 0.90 for both studies (Ranells and Wagger, 1996; Starovoytov et al, 2010). These estimates are consistent with our estimates for hairy vetch and mixtures, but greater than our estimates for pure cereal rye.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have cautioned that legume N residue needs to be managed properly in order to increase N synchrony with crop uptake demands (Crews and Peoples 2005;Gardner and Drinkwater 2009), and to improve legume-N retention (Hauggaard-Nielsen et al 2009;Starovoytov et al 2011). Even in semiarid Saskatchewan, a 17-year old LGM (lentil)-W-W rotation led to higher NO 3 -N leaching than a F-W-W control when the N supplying capacity of the soil was underestimated (Campbell et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen availability is affected by the quantity and quality of these inputs. For legumes, quality is based on characteristics such as the C:N ratio and lignin : N ratio (Kumar and Goh 1999, Cook et al 2010, Starovoytov et al 2010, while manure quality is determined by C:N, organic N : inorganic N, and NH 4 þ : NO 3 À ratios (Loecke et al 2012). Though greater attention has been paid to manipulating the quality of organic inputs to optimize N provision, legume-and manure-derived N can be asynchronous with plant uptake and contribute to N loss (Jensen 1994, Loecke et al 2012.…”
Section: Introductionmentioning
confidence: 99%